P6 Improvements in social determinants and declines in adolescent pregnancy and child marriage in rural uganda, 1994–2018. (18th November 2019) - Santelli, JS; Chen, I; Spindler, E; Nalugoda, F; Lindberg, L; Lutalo, T; Wawer, M; Ssewamala, F; Grilo, S; Kreniske, P; Hoffman, S; Kagaayi, J; et al.
Abstract : Aims: To identify the relationships among social determinants, public policies, behaviors, and adolescent pregnancy and child marriage – in the context of a declining HIV epidemic in the Rakai region of rural Uganda. Social determinants may influence key adolescent social transitions such as leaving school, marriage, and childbearing. Methods: Data on young women 15-19 years from 17 surveys (1994-2018) in a population-based, open cohort of households in 28 communities followed continuously since 1994. Social determinants included school enrollment, a household assets measure of socioeconomic status (SES), and orphanhood (death of one or both parents). A previously validated measure (the Pregnancy Risk Index or PRI) was used to estimate young women's risk of becoming pregnant - based on their sexual activity, nonuse of contraception or use of specific contraception methods, and method-specific contraceptive failure rates. The PRI was compared with current pregnancy, based on self-report and urine testing. Child marriage was measured as ever-married before age 18. Statistical evidence for change over time was assessed using regression analyses with robust variance estimation. The sample included 15, 606 women-rounds of observation. Results: School enrollment rose from 26% in 1994 to 61% in 2018 (p<0.001), coinciding with a national policy of universal primary education instituted in 1997 and considerable increases in household SES. Rates of orphanhood declined from 52% in 2004 to 23% to 2018 (p<0.001), corresponding to availability in antiretroviral therapy from 2004. Child marriage among women 15-19 years declined from 33% to 4% (p<0.001). Current pregnancy declined by 65%; a parallel 58% decline in the average PRI score reflects a decline in sexual experience (67% to 40%) and increases in current contraception use (29% to 42%, all trends p<0.001). Adjusted for age and survey rounds, school enrollees compared to non-enrollees reported less sexual experience (43% vs. 79%, p<0.001), greater use of condoms (55% v 20%, p<0.001) and greater use of any contraceptive method (61% v 39%, p<0.001). Conclusions: Adolescent pregnancy and child marriage declined from 1994 to 2018 as enrollment in school and socioeconomic status increased and HIV-related orphanhood declined. Social determinants can have an enormous influence on adolescent health and social transitions.